What's in a realist configuration? Deciding which casual configurations to use, how, and why - De Weger, E; Van Vooren, NJE; Wong, G; Dalkin, S; Marchal, B; Drewes, HW; Baan, CA (SAGE Publications, 2020)
Background: Realist studies represent an increasingly popular approach for exploring complex interventions’ successes and failures. The theory-driven approach seeks to explain “what works, how, why, in which contexts, for whom, and to what extent” using context–mechanism–outcome (CMO) configurations. When the approach was first developed, CMO configurations were the method for expressing causal explanations. Increasingly, realist studies have been conducted using different variations of the heuristic such as strategy–context–mechanism–outcome (SCMO) configurations or intervention–context–actor–mechanism–outcome (ICAMO) configurations. Researchers have highlighted a lack of methodological guidance regarding which additional explanatory factors can be included in configurations (e.g., strategies, interventions, actors). This article aims to clarify and further develop the concept of configurations by discussing how explanatory factors could be robustly added to the original CMO configuration as put forward by Pawson and Tilley.